Efficacy and Safety of 7.2 J/cm2 Accelerated Corneal Cross-Linking in Pediatric and Adult Keratoconus: A Comparative Study - Turunç, Mustafa; Özdemir, Ahmet; Can, Ertuğrul (Korean journal of ophthalmology, 2025)
Purpose: To evaluate and compare the short-term outcomes of an accelerated corneal cross-linking (CXL) protocol with a total energy dose of 7.2 J/cm2 in pediatric and adult keratoconus patients.Methods: This study included 113 eyes of 82 keratoconus patients who underwent accelerated epithelium-off CXL (12 mW/cm2 for 10 minutes) at a university hospital. Patients were divided into two groups based on age: <18 years (group 1, 48 eyes; mean age, 15.4 ± 1.6 years) and ≥18 years (group 2, 65 eyes; mean age, 23.4 ± 3.4 years). Preoperative and postoperative (6-month) uncorrected visual acuity, best-corrected visual acuity, keratometric indices, central corneal thickness, and endothelial cell density were analyzed and compared between groups.Results: Significant improvements in best-corrected visual acuity and reductions in keratometric indices were observed in both groups (p < 0.05). While both groups demonstrated significant visual and structural improvements, group 2 exhibited a greater magnitude of change in most keratometric and refractive parameters. Both groups exhibited significant decreases in central corneal thickness (p < 0.001). Posterior keratometric values showed statistically significant changes in both groups (p < 0.001). Endothelial cell density remained stable, and no severe complications were noted.Conclusions: Accelerated CXL with a total energy dose of 7.2 J/cm2 demonstrated a favorable safety profile and significant efficacy in stabilizing keratoconus in both pediatric and adult patients over a 6-month period. Notably, adult patients exhibited a greater extent of keratometric and refractive improvement, suggesting a potentially age-dependent biomechanical response. These findings support the utility of this protocol as an early intervention strategy, particularly in young adults with progressive disease.